Histidine triad nucleotide‐binding proteins HINT1 and HINT2 share similar substrate specificities and little affinity for the signaling dinucleotide Ap4A. Issue 10 (17th February 2020) - Strom, Alexander; Tong, Cher Ling; Wagner, Carston R.
Abstract : Human histidine triad nucleotide‐binding protein 2 (hHINT2) is an important player in human mitochondrial bioenergetics, but little is known about its catalytic capabilities or its nucleotide phosphoramidate prodrug (proTide)‐activating activity akin to the cytosolic isozyme hHINT1. Here, a similar substrate specificity profile ( k cat / K m ) for model phosphoramidate substrates was found for hHINT2 but with higher k cat and K m values when compared with hHINT1. A broader pH range for maximum catalytic activity was determined for hHINT2 (pK1  = 6.76 ± 0.16, pK2  = 8.41 ± 0.07). In addition, the known hHINT1‐microphthalmia‐inducing transcription factor‐regulating molecule Ap4 A was found to have no detectable binding to HINT1 nor HINT2 by isothermal titration calorimetry. These results demonstrate that despite differences in their sequence and localization, HINT1 and HINT2 have similar nucleotide substrate specificities, which should be considered in future proTide design and in studies of their natural function. Abstract :